Effect of Reinforcement of Hydrophobic Grade Banana (Musa ornata) Bark Fiber on the Physicomechanical Properties of Isotactic Polypropylene. (17th May 2016) - Mamunur Rashid, Md.; Samad, Sabrin A.; Gafur, M. A.; Rakibul Qadir, Md.; Chowdhury, A. M. Sarwaruddin
Abstract : This research studied the physicomechanical as well as morphological properties of alkali treated (NaOH and KMnO4 ) and untreated banana bark fiber (BBF) reinforced polypropylene composites. A detailed structural and morphological characterization was performed using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and mechanical properties testing (tensile strength, flexural strength, and microhardness). Chemical treatments improved the hydrophobic property of the fiber and it is found to be better for KMnO4 treatment. Composites with 0, 5, 10, and 15 wt.% loadings were then compared for water uptake studies and revealed that KMnO4 treated fiber composites absorb less water compared to others. KMnO4 treatment with 15% fiber loading improved the tensile strength, flexural strength, and microhardness of the composites compared to raw and NaOH treated fiber loadings. TGA analysis also shows onset temperature at 400 500°C that is associated with the decomposition of the banana fibers constituents including lignin, cellulose, and hemicelluloses which suggests better thermomechanical stability. All of the values suggest that 15% KMnO4 treated banana bark fiber (BBF)/PP composites were found to be better than those of the raw and NaOH treated ones.